Vrednote "protestantske etike" v sodobni primerjalni perspektivi - Klanjšek, Rudi (Teorija in praksa, 2016)
Weber's work on the origins of capitalism is one of the classical sociological works. As indicated by Weber, modern (rational) capitalism was formed via a specific set of ideas, i.e., through Protestant motivation that led to methodical work, savings and the accumulation of wealth. Although the theory was previously tested (and criticised), its use is still popular, especially in the context of "development studies". Based on data from WVS (1999-2004), the current study analysed the presence/absence of certain core values of the Protestant ethic in four different regions (Protestant European countries, Non-Protestant European countries, (Post)transition European countries, and the USA). The results indicated that the importance of hard work, a typical element of Protestant ethics, was lowest in countries with a Protestant tradition, and highest in the (Post)transition societies. This can be interpreted in the context of time (e.g., Weber's hypothesis was valid in the previous historical periods), although the results may also be seen in the light of the low validity of the hypothesis itself.
Keywords: Comparative analysis; Javno mnenje; Primerjalna analiza; Protestant ethics; Protestantska etika; Public opinion; Values; Vrednote